Penegakan Hukum terhadap Satuan Pengamanan (Satpam) yang Menjalankan Fungsi dan Tugasnya Berdasarkan Pasal 49 KUHP - Jonathan Wesley; Syahrul Machmud; Hernawati RAS (CV Rewang Rencang, 2023)
The Security Unit or abbreviated as Security Guard based on Chief Of Police Regulations Number 4 of 2020 concerning Swakarsa Security is a profession carrying out limited police functions. The dilemma of the Security Guard occurs when facing a criminal event, with its limited role having to carry out forced self-defense as stipulated in Article 49 of the Indonesia Criminal Code, because otherwise unwanted things will happen to the company's assets guarded by the Security Guard, and may even endanger the life of the Security Guard. To provide legal protection for security guards who are vulnerable to crime, the regulations are not only rules made by the Chief of Police but also regulated explicitly through laws and regulations.